ESTERASE AS A MARKER FOR IDENTIFICATION OF GENETIC VARIATIONS IN COLDWATER FISH, SCHIZOTHORAX RICHARDSONII (GRAY) - Kapila, Rajeev; Mishra, D P (Journal of the Inland Fisheries Society of India, 2016)
ESTERASE AS A MARKER FOR IDENTIFICATION OF GENETIC VARIATIONSIN COLDWATER FISH, SCHIZOTHORAX RICHARDSONII (GRAY)